Rare missense mutations in RECQL and POLG associate with inherited predisposition to breast cancer. Issue 11 (31st January 2018) - Tervasmäki, Anna; Mantere, Tuomo; Hartikainen, Jaana M.; Kauppila, Saila; Lee, Hang‐Mao; Koivuluoma, Susanna; Grip, Mervi; Karihtala, Peeter; Jukkola‐Vuorinen, Arja; Mannermaa, Arto; Winqvist, Robert; Pylkäs, Katri
Abstract : Several known breast cancer susceptibility genes with moderate‐to‐high risk alleles encode proteins involved in DNA damage response (DDR). As these explain less than half of the hereditary breast cancer cases, additional predisposing alleles are likely to be discovered. Many of the previous studies utilizing massive parallel sequencing have focused on the protein‐truncating variants, and the role of rare missense mutations has remained poorly addressed. To identify novel susceptibility factors, we have systematically analyzed the data from our parallel sequencing of 796 DDR genes in 189 Northern Finnish hereditary breast cancer patients for rare missense variants, predicted as deleterious. Thirty‐five variants were studied here for the disease association using Finnish breast cancer case ( n  = 492–2, 035) and control ( n  = 277–1, 539) cohorts. As a result, two missense variants in genes involved in DNA replication, RECQL p.I156M and POLG p.L392V, the former involving genomic and the latter mitochondrial DNA replication, showed significant association with risk of breast cancer. Rare RECQL p.I156M allele was observed in breast cancer cases only (6/1, 946, 0.3%, p  = 0.043), whereas POLG p.L392V was two times more frequent in breast cancer cases (53/2, 238, 2.4%) compared to controls (18/1, 539, 1.2%, OR = 2.1, 95% CI 1.2–3.5, p  = 0.010). Based on the current genetic data, both RECQL p.I156M and POLG p.L392V represent novel breast cancer predisposing alleles. Abstract : What's new? Evidence suggests that some missense mutations might increase cancer risk even more than other types of mutation. In this study, the authors identified two missense variants that were associated with an increased risk of breast cancer. These mutations occurred in RECQL and POLG genes involved in DNA repair. The identification of new susceptibility alleles provides new tools for clinical risk assessment in individuals with a family burden of breast cancer. These results also further support a link between defective DNA damage response and breast cancer susceptibility.